Peningkatan Digitalisasi Desa Wisata Melalui Branding Strategi di Indonesia : Digitalisasi Desa Wisata - Nurafifah, Syifa Annisa; nurmandi, achmad; fridayani, helen dian (Journal of Governance Innovation, 2024)
In the context of digitalization of tourist villages there are several indicators to be able to realize digitalisation of tourism villages including promotion, pricing, place, attraction, partnership, and accessibility. The aim of this study is to understand how to improve the digitization of tourist villages in Indonesia through the use of branding strategies. The method used in this research is a method of qualitative analysis using secondary data sources from mass media news, journals, articles processed using Vosviewers Software and Nvivo 12 as a form of data visualization. The results of this research are obtained results that by using branding strategy digitalization of tourist villages in Indonesia has been improved. One of the successes in using branding strategy is with increased indicators of promotion, partnership and attraction. This is supported by some evidence, one of which according to the Digital Global Overview Report Indonesia shows that YouTube is one of the media for the promotion of tourist villages. And based on Jadesta.Kemenparekraf showed that the most attractive tourist village in Indonesia is showing the beauty of nature. Keywords: Tourism digitalization, Village tourism, Branding Strategy